(untitled) (Washington DC, 2005)
Assessment of Resource Flows in the Water Supply and Sanitation Sector. Ethiopia Case Study. Peter L. Watson, Joseph Gadek, Eyob Defere, Catherine Revels. This case study reports on the work undertaken to collect data for the Background Paper for the Water Supply and Sanitation (WSS) Chapter of the Ethiopia 2003 Public Expenditure Review (PER). The Background Paper was based on discussions with various stakeholders, and a synthesis of available studies and consultant reports. The study appears to have been the first attempt to consolidate all expenditures for the Ethiopian WSS sector to give an indicative picture of the level of funding, in both absolute terms and per capita figures. The results are alarming; the low levels of investment clearly explain why the levels of service are so dreadfully low.
Keywords: Water supply,Sanitation,Cung cấp nước,Vệ sinh; Ethiopia,Ethiopia,Ethiopia,Ethiopia